Crystal structure of catena-poly[[trimethyltin(IV)]-μ-2-(2-nitrophenyl)acetato-κ2O:O′]. (March 2015) - Danish, Muhammad; Tahir, Muhammad Nawaz; Iftikhar, Sana; Raza, Muhammad Asam; Ashfaq, Muhammad
No abstract available